Moldova Climate Adaptation Investment Planning - World Bank (Washington, DC, 2017)
Moldova ranks as the most climate vulnerable country in Europe, according to the widely used NDGAIN vulnerability assessment methodology. Temperature and rainfall have increased in Moldova over the last century, and severe floods and droughts have been occurring more regularly in recent times. For example, in the years prior to 2007, average annual losses from climate-related disaster losses were estimated at over USD60m per year, but in the same year, a severe drought occurred which was later assessed to have caused around USD1 billion of damage and losses. Looking forward, climate models predict further mean temperature rises and more variable rainfall with anything from a slight increase to a significant decline in total precipitation. Even under scenarios with an increase in mean rainfall, however, water availability will decrease due to increased temperatures and rates of evapotranspiration. Rainfall will also become more variable and more concentrated due to the more common extreme events. In general, climate adaptation issues in Moldova have been well characterized. The National Climate Change Adaptation Strategy identifies six sectors at particular risk. Agricultural productivity will significantly decrease due to increasing water stress on crops, even without accounting for the increasing impact of extreme weather events (i.e., hailstorms and late frosts, major floods and droughts, or changes in patterns of disease and pests). Total water availability will fall below total demand within a couple of decades. Health effects of climate change will include increases in heat related ailments (including cardio-vascular disease), transmission of gastro-intestinal diseases, air pollution and allergies, as well as higher numbers of casualties from natural disasters. The productivity of forests will diminish and pathology patterns are expected to change. Peak energy consumption patterns will shift from the winter to the summer, energy distribution and transmission infrastructure may also be impacted and the country’s potential to reduce energy imports through development of renewable sources (mainly solar, biomass, wind, and geothermal) could be compromised. Transport infrastructure could be disrupted. The current study extends existing analyses through a quantitative assessment of adaptation investment opportunities and returns across the target sectors. To achieve this, the study evaluated the cost of inaction in each sector, i.e., the expected annual opportunity cost of not being better adapted to prevailing climate conditions.